ORGANIZATIONAL PSYCHOLOGICAL OWNERSHIP AND INNOVATIVE WORK BEHAVIOR: MEDIATING EFFECT OF KNOWLEDGE HIDING - Rully; Rrin Handayani; Fahmi Oemar; Didik Siswanto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Innovation is a crucial element for organizational sustainability and competitiveness in a dynamic era. This study aims to examine the effect of Organizational Psychological Ownership (OPO) on Innovative Work Behavior (IWB), as well as to analyze the mediating role of Knowledge Hiding in this relationship. Grounded in organizational psychology theory, psychological ownership toward the organization is expected to foster innovative work behavior by suppressing knowledge-hiding behaviors among employees. This study adopts a quantitative approach using a survey method distributed to employees in [mention sector/industry, e.g., the banking/tech sector]. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that OPO has a significant positive effect on IWB and a negative effect on Knowledge Hiding. Furthermore, Knowledge Hiding is proven to mediate the relationship between OPO and IWB. These findings highlight the importance of nurturing employees' sense of ownership to minimize knowledge hiding, thereby encouraging workplace innovation. Practical implications and suggestions for organizational management are also discussed.